EFEKTIVITAS MEMBACA KOMIK DAN METODE STORYTELLING DALAM MENINGKATKAN PENGETAHUAN SISWA TENTANG SARAPAN SEHAT - Nababan, Sudarwati; Tete, Maria Ovianista (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2024)
House Breakfast should be a healthy breakfast. A healthy breakfast contains the nutrients the body needs to carry out daily physical activities, increases endurance and supports children's growth. The aim of this research is to analyze the effectiveness of health education, reading comics and storytelling methods, in increasing students' knowledge about healthy breakfasts. This research is quasi-experimental research with a nonequivalent control group design. A sample of 45 students was taken using quota sampling technique. The sample was divided into 3 groups (intervention group 1, intervention group 2 and control group), each group had 15 respondents. The reason for the number 15 is because it considers the effectiveness of small group health education. The comic media used in this research is the health literacy comic series published by Pendidikan.id. The results of the research showed that there was an increase in students' knowledge after health education had a p-value of 0.000. Comic reading education and storytelling method comic education are equally effective in increasing students' knowledge. Comics are an alternative educational media that is suitable for elementary school children.